Evolution of official social networks of the Universidad Tecnica Particular de Loja - Ecuador [Evolución de las redes sociales oficiales de la Universidad Técnica Particular de Loja - Ecuador] - Marin Gutierrez, I. (2015)
The phenomenon of social networking is changing the way we interact and spending our free time. In social networks we are constantly seeking contact with people and institutions to be dealing, maintain old friends, catch up with others, meet new people or even find work. In our particular we analyze the evolution of social networks in a private university in Ecuador, the Universidad Tecnica Particular de Loja. The results have been continued increases in followers on Facebook and Twitter accounts UTPL. © 2015 AISTI.